Late Quaternary Relative Sea-Level Change on the West Coast of Newfoundland - Bell, Trevor; Daly, Julia; Batterson, Martin; Liverman, David; Shaw, John; Smith, I. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractTwo revised relative sea-level (RSL) curves are presented for the Port au Choix to Daniel’s Harbour area of the Great Northern Peninsula, northwestern Newfoundland. Both curves are similar, showing continuous emergence of 120-140 m between 14 700 cal BP and present. The half-life of exponential curves fit to the RSL data is 1400 years and the rate of emergence varies from ~2.3 m per century prior to 10 000 cal BP to ~0.13 m per century since 5000 cal BP. The curves fit a general pattern of RSL history along the west coast of Newfoundland, where there is a southward transition from solely emergence to emergence followed by submergence. Isostatic depression curves are generated for four RSL records spanning the west coast. Almost double the crustal depression is recorded to the northwest, reflecting the greater glacioisostatic loading by the Laurentide Ice Sheet over southern Labrador and Québec compared to a smaller loading centre by a regional ice complex over Newfoundland. Only the St. George’s Bay RSL record in the southwest appears to show evidence for a proglacial forebulge, when at 6000 cal BP an isostatic ridge of 4 m amplitude begins to collapse.